The special developmental biology of craniofacial tissues enables the understanding of oral and maxillofacial physiology and diseases - Weber, Manuel; Wehrhan, Falk; Deschner, James; Sander, Janina; Ries, Jutta; Möst, Tobias; Bozec, Aline; Gölz, Lina; Kesting, Marco Rainer; Lutz, Rainer (International Journal of Molecular Sciences, 2021)
Maxillofacial hard tissues have several differences compared to bones of other localiza-tions of the human body. These could be due to the different embryological development of the jaw bones compared to the extracranial skeleton. In particular, the immigration of neuroectodermally differentiated cells of the cranial neural crest (CNC) plays an important role. These cells differ from the mesenchymal structures of the extracranial skeleton. In the ontogenesis of the jaw bones, the development via the intermediate stage of the pharyngeal arches is another special developmental feature. The aim of this review was to illustrate how the development of maxillofacial hard tissues occurs via the cranial neural crest and pharyngeal arches, and what significance this could have for relevant pathologies in maxillofacial surgery, dentistry and orthodontic therapy. The pathogenesis of various growth anomalies and certain syndromes will also be discussed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cranial neural crest; Developmental biology; Maxillofacial development; Orthodontics